Deforestation caused abrupt shift in Great Lakes nitrogen cycle. (6th March 2020) - Guiry, Eric J.; Buckley, Michael; Orchard, Trevor J.; Hawkins, Alicia L.; Needs‐Howarth, Suzanne; Holm, Erling; Szpak, Paul
Abstract: Despite the longstanding significance of North America's Great Lakes, little is known about their preindustrial ecology. Here, we report on when and how humans first became a main driver of Lake Ontario's nutrient dynamics. Nitrogen isotope analyses of archaeological fish show that, prior to the 1830s, Lake Ontario's nitrogen cycle and the trophic ecology of its top predators had remained stable for at least 800 yrs, despite Indigenous and historical European agricultural land management across the region. An abrupt shift in the nitrogen isotope composition of Lake Ontario's fish community is evident in the early to mid‐19 th century and reflects the initiation of industrial‐scale forest clearance. These data show how the nitrogenous nutrient regimes of even the world's largest freshwater ecosystems can be highly sensitive to short‐term watershed forest cover disturbances and indicate a profound shift in the relationship between humans and their environment.